CONSISTENCY OF THE NATIONAL CAPITAL AUTHORITY AS A SPECIAL REGIONAL GOVERNMENT WITH THE CONSTITUTION - F. Putuhena, M Ilham (NOMOI Law Review, 2023)
With the various specialties that exist in the Archipelago Capital City, both related to the implementation of the Special Regional Government for the Archipelago Capital City and the implementation of preparation, development and relocation activities for the National Capital City, it is expected that various problems will arise, including, among other things, unclear division of affairs, tug-of-war and overlap. Overlapping authority between the Central Government and the regional government administering the National Capital in various matters and government affairs no longer occurs in its implementation. The method used in this research is normative juridical law research method. Based on article 18 paragraph (1) of the 1945 NRI Law, Indonesia is the Unitary State of the Republic of Indonesia divided into provinces and the provinces are divided into districts and cities